Gestión de ingresos de la distribuidora Touma S. A. Ditosa de los años 2019-2020. - Monserrate Bastidas, Arelis Daniela (2022)
The Touma S.A Ditosa Distributor with RUC number: 1290071700001 with economic activity: sale of construction materials such as: bricks, gravel, cement, rods and finishes for the home, etc. It was created in 1997 and is currently located on Malecon 9 de October (Esq.). 100 Mejía belonging to Babakoto-Los Ríos, place of reference La carreta Restaurant, belongs to a Disensa franchisee, due to its low costs and quality of the materials it has a good acceptance in the market which allowed the expansion of the premises with the area from hardware store. In 2020, a health emergency called COVID-19 occurred, this caused businesses to close for a certain time, taking into account the measures dictated by the National Emergency Operation Center and, as an economic effect, this virus caused a reduction in sales. which was corroborated by applying the horizontal financial analysis to its Income obtained from the Statements of Comprehensive Income for the periods 2019-2020. This information was collected through interviews as a deductive research method in conjunction with the company's management, managing to determine the problem of managing their income on the effects of the pandemic, Income management is the heart of every company. market oriented. This research was developed within the research subline, Financial, tax and social commitment management, of the accounting and auditing career, of the Faculty of Administration, Finance and Information Technology of the Technical University of Babahoyo.